2022
DOI: 10.1134/s0010508222040128
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Thermal Gasification of Organic Wastes

Abstract: This paper presents the results of computational and experimental studies of the electroplasma gasification of carbon-containing technogenic wastes to obtain high-calorific-value syngas (H 2 + CO) for power-generating devices. The composition of the syngas produced by gasification of organic wastes was experimentally determined. The change in the composition and calorific value of the syngas depending on the gasification time of organic materials was studied. The change in the calorific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…An'shakov et al conducted experiments on organic wastes using a two-stage process with plasma usage in both reactors. 209 A first plasma torch is used in the gasifier, while an electric-arc plasma torch in the second reactor maintains the temperature at 1300-1500 1C. 209,210 Vishwajeet et al conducted experiments using a two-stage gasification system coupling a prototype-entrained flow plasma-assisted gasification reactor with ex-situ plasma vitrification.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An'shakov et al conducted experiments on organic wastes using a two-stage process with plasma usage in both reactors. 209 A first plasma torch is used in the gasifier, while an electric-arc plasma torch in the second reactor maintains the temperature at 1300-1500 1C. 209,210 Vishwajeet et al conducted experiments using a two-stage gasification system coupling a prototype-entrained flow plasma-assisted gasification reactor with ex-situ plasma vitrification.…”
Section: Reviewmentioning
confidence: 99%
“…209 A first plasma torch is used in the gasifier, while an electric-arc plasma torch in the second reactor maintains the temperature at 1300-1500 1C. 209,210 Vishwajeet et al conducted experiments using a two-stage gasification system coupling a prototype-entrained flow plasma-assisted gasification reactor with ex-situ plasma vitrification. 211 They showed that although the use of plasma positively affects the quality of the raw syngas, the dilution by plasma gases such as N 2 leads to a low calorific value of the dry syngas.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 99%